2012
DOI: 10.1021/np300095c
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Sesquiterpenoids from the Rhizomes of Acorus calamus

Abstract: Eight new sesquiterpenes (1-8) and one new norsesquiterpene (9) named calamusins A-I were isolated from the ethanol extract of Acorus calamus rhizomes. The absolute configuration of compound 8 was determined by comparing its experimental and calculated ECD spectra. The absolute configurations of the other compounds were determined from their CD spectra. Furthermore, in in vitro assays, compounds 3, 4, 7, and 9 (10 μM) exhibited weak hepatoprotective activities against APAP-induced HepG2 cell damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 18 publications
2
38
0
Order By: Relevance
“…The functional group at C-7 lying in the back lower left area was responsible for the negative Cotton effect (n−π*), which was consistent with the Cotton effect at 335 nm (Δε −19.0). Moreover, the ECD helicity rule of α,β-unsaturated ketones 16 was used to further confirm the absolute configuration of compound 3 . The P -helicity of the O=C–C α =C β torsion angle correlates the positive Cotton effect (π–π*) at 297 nm (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…The functional group at C-7 lying in the back lower left area was responsible for the negative Cotton effect (n−π*), which was consistent with the Cotton effect at 335 nm (Δε −19.0). Moreover, the ECD helicity rule of α,β-unsaturated ketones 16 was used to further confirm the absolute configuration of compound 3 . The P -helicity of the O=C–C α =C β torsion angle correlates the positive Cotton effect (π–π*) at 297 nm (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Previous phytochemical studies on A . calamus revealed the presence of sesquiterpenes, flavones, phenylpropanoids, alkaloids, etc . Bioactivity studies showed that the crude extract of A .…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 1 and 2 were tested for hepatoprotective activity in the N -acetyl- p -aminophenol (APAP)-induced toxicity model in HepG2 (human hepatocellular liver carcinoma cell line) cells, using the hepatoprotective drug bicyclol as the positive control 15 . As shown in Table 2, compound 1 exhibited moderate hepatoprotective activity.…”
Section: Resultsmentioning
confidence: 99%